Sistem Pakar Deteksi Penyakit Ginekologi Menggunakan Metode Forward Chaining - Anita Ratnasari; Yuwan Jumaryadi; Grace Gata (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Gynecological disease is a disease that is feared by women. Several diseases related to gynecological diseases such as uterine fibroids, uterine cysts, cervical cancer are types of gynecological diseases. This research develops an expert system to help detect gynecological diseases using the forward chaining method. The system development method used in this research is waterfall. The waterfall method consists of 5 stages, namely planning, analysis, design, implementation, and system. By developing this system, it can help detect gynecological diseases early based on existing symptoms so as to prevent the negative effects of these diseases.